Vitamin and mineral status within various tissues of bison: a scoping review - Okoren, Claire; Engle, Terry; Edwards-Callaway, Lily (Frontiers in Conservation Science, 2025)
The North American bison (Bison bison) is gaining prominence in agricultural production systems across North America; however, comprehensive species-specific management guidelines, particularly regarding nutrition, remain limited. Vitamins and minerals are critical components of animal nutrition, playing essential roles in health maintenance and productivity. As bison production expands, the demand for precise nutritional benchmarks tailored to the species becomes increasingly evident. This scoping review aimed to (1) synthesize existing data on vitamin and mineral concentrations in bison tissues and (2) identify gaps in the current knowledge base to enhance bison health, welfare, and productivity. The review evaluated literature addressing vitamin and mineral profiles across various tissues in bison, while highlighting emerging areas of research, including the influence of environmental conditions and feeding systems (e.g., grass- versus grain-finished diets) on micronutrient status. Furthermore, although limited data were available, initial findings suggest sex and age do not impact micronutrient concentrations in bison tissues. These results underscore the need for further targeted research to refine and advance our understanding of micronutrient status of bison in order to develop a robust baseline data set to begin experiments to determine mineral and vitamin requirements for bison.